The impact of cognitive flexibility on resistance to organizational change and employee turnover intention: A study at Pertamina Geothermal Energy Tbk - Wulandari, Ratna Indah; Yuningsih (Lighthouse Publishing, 2025)
Organizational change is an inevitability in a dynamic business environment, yet it is often hindered by employee resistance. Cognitive flexibility, defined as an individual’s ability to adapt to change, is believed to play a crucial role in reducing both resistances to change and employee turnover intention. This study aims to analyze the influence of cognitive flexibility on resistance to organizational change and employee turnover intention at Pertamina Geothermal Energy Tbk. A quantitative method was employed, with a sample of 170 permanent employees selected through non-probability sampling using a convenience sampling technique. Data analysis was conducted using simple linear regression and partial tests with IBM SPSS Statistics 25. The results support the proposed hypotheses, indicating that cognitive flexibility has a significant negative effect on resistance to organizational change, as well as a significant negative effect on employee turnover intention. Based on these findings, it is recommended that Pertamina Geothermal Energy Tbk develop training programs focused on enhancing adaptability, problem-solving skills, and fostering a growth mindset to improve employees’ cognitive flexibility. The company is also encouraged to actively engage employees in the change process through innovative training such as creative workshops and interactive communication strategies to minimize resistance. Furthermore, strong cognitive flexibility contributes to lowering turnover intention, making it important for the company to integrate cognitive development into long-term retention strategies, such as clear career paths and the creation of a supportive and inclusive work culture.